Khayalak TV di Indonesia - Putri, Ariana (LANCAH: Jurnal Inovasi dan Tren, 2024)
Television as a mass media which is almost in a century became the most preferred mass media at this time began to be disrupted by the presence of new media, namely social media. This new media is growing in the country which makes Indonesia one of the highest internet users in the world. Nearly half of Indonesia's population is currently an internet user, they access the internet generally from smart phones or smartphones. Indonesian mass media audiences (especially the younger generation) have now switched to the use of media, not only the print media that are increasingly unsold, but also affect television media. The pattern of watching TV has changed. The audience is not completely transfixed by the broadcast hours and broadcast time. In the internet era, people can watch TV anytime and anywhere. In addition, watching TV shows does not always have to be from a television set, but many viewers, especially millennials who watch through gadgets, smartphones or laptops. Television broadcasting is currently strictly regulated and supervised by the government through the Indonesian Broadcasting Commission, but social media is still very free because there are no specific regulations. The audience can watch anything including spectacle which is strictly prohibited to be broadcast on television, through social media a prohibited spectacle is very easy and free to be watched by anyone.